KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU DI SD NEGERI 1 BALAU KENCANA KEDAMAIAN KOTA BANDAR LAMPUNG - Herli Sarpani; Erjati abas; Etika Pujianti (UNISAN JURNAL, 2022)
The principal has a very influential role in the school environment for which he is responsible. The principal’s task as a leader is to help teachers develop their abilities to the maximum and create a healthy school life atmosphere, encourage teachers, administrative staff, students and parents to unite their thoughts and actions in effective collaborative activities to achieve goals. school. In this study, the researcher used a qualitative approach. Qualitative research is a research approach that uncovers certain social situations by describing reality correctly, formed by words based on data collection techniques and analysis of relevant data obtained from natural situations. This research in addition to describing in depth about the leadership of the principal, also analyzes the approach used and the factors that influence the structure of the implementation of his leadership. The results showed that the implementation of the Principal’s Leadership at SD Negeri 1 Kali Balau Kencana Kesejahteraan Bandar Lampung City was quite good, in this case the Principal’s Leadership in order to improve the professional competence of teachers was quite dominant. Keywords: Leadership, Improving Elementary Teacher Professional Competence